THINKING ABOUT CORRUPTION - Westerman, Pauline (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract In this article, corruption is analyzed as behaviour of officials who implement the law but do not treat the law as exclusionary reasons for decision-making. It is proposed that in order to understand such a failure of law, the conditions should be examined in which law is successful. Philosophical literature as well as empirical studies seem to consider that legal orders are only successful if they are either based on morality or on coercion. Both considerations also play an important role in empirical research that seeks to find remedies either in moral education or in sanctions and incentives. This article proposes a third explanation for the success of a legal order, wherein law is not seen as a restriction of freedom and power, but rather extending and transforming the competence and rights of power to officials and citizens. Therefore, both may be inclined to maintaining the legal order to which they owe their competencies. This thought experiment, in turn, generates two theoretical hypotheses that should be tested by empirical research: the first is that a legal order should confer powers to a wider range of participants to maximize stability and long-term self-interest; the second is that powers, licences, and rights should be granted liberally to avoid the situation of corrupting power due to its scarcity. Abstract Dalam artikel ini, korupsi dilihat sebagai perilaku pejabat yang menerapkan hukum tetapi tidak memperlakukan hukum sebagai alasan pengecualian dalam mengambil keputusan. Untuk memahami kegagalan hukum, hukum harus dianalisis saat sedang berhasil. Studi secara filosofis maupun empiris beranggapan bahwa perintah hukum hanya akan berhasil jika didasarkan pada moralitas atau paksaan. Kedua anggapan tersebut penting dalam mencari solusi baik dalam pendidikan atau sanksi dan insentif. Artikel ini menawarkan penjelasan ketiga untuk keberhasilan tatanan hukum, di mana hukum tidak dilihat sebagai pembatasan kebebasan dan kekuasaan. Namun, hukum memperluas dan memberi transformasi terhadap kompetensi dan hak-hak kekuasaan pada pejabat dan warga negara. Oleh karena itu, keduanya cenderung mempertahankan tatanan hukum yang menjadi tanggung jawab mereka. Hal ini, pada gilirannya, menghasilkan dua hipotesis teoretis yang harus diuji: pertama, tatanan hukum harus memberikan kekuasaan kepada peserta yang lebih luas untuk memaksimalkan stabilitas dan kepentingan pribadi jangka panjang; dan kekuasaan, izin, dan hak-hak harus diberikan secara bebas kepada kelangkaan kekuasaan untuk menghindari kekuasaan yang korup.